2018
DOI: 10.1155/2018/2159702
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Retinal Photographs to Entropy Images in Deep Learning to Improve Automated Detection for Diabetic Retinopathy

Abstract: Entropy images, representing the complexity of original fundus photographs, may strengthen the contrast between diabetic retinopathy (DR) lesions and unaffected areas. The aim of this study is to compare the detection performance for severe DR between original fundus photographs and entropy images by deep learning. A sample of 21,123 interpretable fundus photographs obtained from a publicly available data set was expanded to 33,000 images by rotating and flipping. All photographs were transformed into entropy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 21 publications
(31 reference statements)
0
42
0
Order By: Relevance
“…We select 21,123 color fundus photographs with good image quality. e experimental setup is the same with that in [18]. e retinal images obtained from the Kaggle e resized images are increased by data augmentation using flipping and rotation.…”
Section: Dataset and Gradingmentioning
confidence: 99%
See 2 more Smart Citations
“…We select 21,123 color fundus photographs with good image quality. e experimental setup is the same with that in [18]. e retinal images obtained from the Kaggle e resized images are increased by data augmentation using flipping and rotation.…”
Section: Dataset and Gradingmentioning
confidence: 99%
“…Artificial intelligence has the potential to revolutionize the traditional diagnosis method for eye disease and bring out a significant clinical impact on promoting ophthalmic health care service [10][11][12][13]. Automated DR detections have been previously studied [14][15][16][17][18]. Deep learning of fundus photograph has emerged as a practical technique for automatic screening and diagnosis of DR. e effective deep learning system is able to correctly and automatically identify severer DR with equal or better accuracy than the trained graders and retina specialists [19], and thus, it can benefit the patients in medically underserved areas that have limited numbers of ophthalmologists and rare medical resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their project achieved accuracy of 99.3% for training and 88.3% for the testing set. Lin et al [15] in their work used deep learning to compare the performance of detection for severe diabetic retinopathy between entropy images and original fundus images. This study showed that using entropy images achieve 86.10%of accuracy, 73.24% of sensitivity, and 93.81% of specificity, whereas achieve 81.80% of accuracy, 68.36%of sensitivity, and 89.87%of specificity while using original fundus images.…”
Section: Related Workmentioning
confidence: 99%
“…The first issue is expertise: a well-trained ophthalmologist is required for DR grading and lesion type assessment. 8,9 The second issue is intergrader reliability: human interpretation of imaging varies among ophthalmologists. 10,11 The third issue is manpower: the compound annual growth rate (CAGR) of the number of eye doctors (CAGR: 2.60%) is lower than that of the diabetic population in Taiwan (CAGR: 4.78%).…”
Section: Introductionmentioning
confidence: 99%